Notch1 switches progenitor competence in inducing medulloblastoma - Ballabio, Claudio; Gianesello, Matteo; Lago, Chiara; Okonechnikov, Konstantin; Anderle, Marica; Aiello, Giuseppe; Antonica, Francesco; Zhang, Tingting; Gianno, Francesca; Giangaspero, Felice; Hassan, Bassem A.; Pfister, Stefan; et al. (Science advances, 2021)
The identity of the cell of origin is a key determinant of cancer subtype, progression, and prognosis. Group 3 medulloblastoma (MB) is a malignant childhood brain cancer with poor prognosis and few candidates as putative cell of origin. We overexpressed the group 3 MB genetic drivers MYC and Gfi1 in different candidate cells of origin in the postnatal mouse cerebellum. We found that S100b(+) cells are competent to initiate group 3 MB, and we observed that S100b(+) cells have higher levels of Notch1 pathway activity compared to Math1(+) cells. We found that additional activation of Notch1 in Math1(+) and Sox2(+) cells was sufficient to induce group 3 MB upon MYC/Gfi1 expression. Together, our data suggest that the Notch1 pathway plays a critical role in group 3 MB initiation.